De novo undifferentiated pleomorphic sarcoma arising from a renal allograft: A case report. (2015) - Mayor, Grégoire; Wirth, Gregory J.; Sanchez-Pareja, Andrea; La Harpe, Romano; Gehrig, Christian; Iselin, Christophe E.
Abstract: To the best of our knowledge, this is the first report of an undifferentiated pleomorphic sarcoma arising from a renal graft. Transplantectomy was performed in a 47-year old woman presenting to the emergency room because of general weakness. Preoperative workup revealed a 5.5 cm malignant mass of the graft which was not present on routine ultrasound performed 12 months earlier. Following transplantectomy, local recurrence developed despite complete tumor resection and interruption of immunosuppression. Despite radiation therapy, the outcome was ultimately fatal. Genetic analysis revealed that the tumor had arisen from donor tissue. Annual ultrasound surveillance might not be enough effective to screen for these rare high grade neoplasms.